Occipital nerve stimulation in a patient with an intractable chronic headache -A case report - Shin, Jae Hyuck; Kim, Yong Chul; Jang, In Ki; Kim, Jae-Hun; Park, Soo Young; Lee, Sang Chul (Korean journal of anesthesiology, 2011)
Occipital nerve stimulation (ONS) is a form of peripheral nerve stimulation used to treat refractory headaches. The trial of ONS was carried with the midline incision C1-2 level, inserted electrical lead subcutaneously to oblique and cephalad direction followed by trajectory of blunt dissection. We used 8 pole electrical lead to cover lesser occipital nerve, greater occipital nerve, third occipital nerve and great auricular nerve. We anchored the lead at the midline insertion site after confirming the stimulation of the patient. And then we looped and tightened the lead loosely, connected the lead and the extension under right supraspinatus muscle region. After 1 week trial period, we performed the permanent implantation of occipital nerve stimulator. We inserted internal pulse generator under a pocket located at right infraclavicular region. The VAS score dropped from 8/10 to 1-2/10. No serious complications were detected during 1 month follow-up.